Value Chains and Competitiveness in Europe : A Comparative Case study of the Czech Republic and Switzerland - Thakur-Weigold, Sarbani Bublu; Hnát, Pavel, 1981-; Jiránková, Martina, 1967-; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2020)
The objective of this dissertation is to bridge the gaps in globalization studies by summarizing the body of global value chains (GVC) knowledge across Economics, Geography, Sociology, International Business (IB), and Operations Management. The study positions itself firmly within the framework of European economic integration, which has received insufficient attention by GVC scholars. To discover possibilities for value creation and enable policy development, it benchmarks two developmentally different, but otherwise comparable, European countries deeply embedded in GVCs: the Czech Republic and Switzerland. In so doing, the thesis addresses two research questions: 1. How to compete as a place and as a firm? And 2. What types of strategy can change the shape of the Smile Curve for the better?
Vedoucí práce: Pavel Hnát
Disertační práce (Ph.D.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2020
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2020
Způsob přístupu: Internet
Keywords: evropská studia [obor disert. práce]; disertace; dissertations